Áreas de risco para raiva humana em Minas Gerais, 1991-1999 - Cristiana Ferreira Jardim de Miranda (2001)
A qualitative-quantitative epidemic study with the objective of identifying and characterizing the different risk areas for the transmission of rabies by dogs and cats in Minas Gerais took place from 1991 to 1999. A descriptive observational retrospective method was used in 25 Regional Health Centers (DRS), linked to the State Secretary of Health (SESMG), as well as semi-structured interviews with each regional program dirextor responsible for the rabies control program. The indicators used were the estimate of the canine population, the ocurrence of canine and feline rabies confirmed by laboratory exams, the notification human rabies, and antirabies vaccination along with the infrastructure of the program in the DRS. The results of 2845 records of laboratory diagnosis were analyzed for canine, feline, and human rabies. The records were obtained from the following sources - Instituto Mineiro de Agropecuária da Secretaria de Estado da Agricultura (The Livestock and Farming Institute of Minas Gerais of the State Secretary of Agriculture), Centro de Controle de Zoonoses da Prefeitura Municipal de Belo Horizonte, (The Center for the Control of Animal Transmitted Diseases of Belo Horizonte). Consolidated reports from 1997 to 1999 of antirabies vaccination acquired from The State Secretary of Health (SESMG) and records of notification of cases of human rabies from the Fundação Nacional da Saúde (FUNASA) - Brasília/ DF (The National Foundation of Health) were also used. The results allowed Minas Gerais to be classified in four different risk modalities; zero, low, medium, and high. The areas of high risk, loocated in the valleys of the Jequitinhonha, Mucuri, and Doce rivers, coincide with areas of lower socioeconomic development. The only area classified as zero is located in the state capital, It has been conclued that the need exits to adapt actions for the control and eradication of human rabies transmitted by dogs and cats using differentiated strategies that are in accord with the specific character of each risk area.